C reactive protein levels are increased in non-allergic but not allergic asthma: a multicentre epidemiological study. Issue 6 (27th May 2005) - Ólafsdottir, I S; Gislason, T; Thjodleifsson, B; Olafsson, Í; Gislason, D; Jögi, R; Janson, C
Abstract : Background: High sensitivity C reactive protein (HsCRP) is an inflammatory marker known to be related to smoking, obesity, and cardiovascular disease. A study was undertaken to determine whether HsCRP is related to respiratory symptoms, asthma, atopy, and bronchial hyperresponsiveness in population samples from three countries. Methods: HsCRP was measured in 1289 subjects from three centres in ECRHS II: Reykjavik, Uppsala and Tartu. The HsCRP values ranged from <0.01 mg/l to 70.0 mg/l and were divided into four equal groups (⩽0.45, 0.46–0.96, 0.97–2.21, and >2.21 mg/l). Results: HsCRP increased with increasing body mass index ( r  = 0.41; p<0.0001) and was higher in smokers than in never smokers (p = 0.02). A significant relationship was found between increased HsCRP levels and respiratory symptoms such as wheeze, attacks of breathlessness after effort, and nocturnal cough (p<0.0001). The crude odds ratio (95% CI) for the probability of non-allergic asthma was 3.57 (1.83 to 6.96) for subjects in the 4th quartile compared with the 1st quartile of HsCRP. This association remained significant after adjusting for study centre, age, sex, body weight, and smoking history (OR 2.19 (95% CI 1.04 to 4.63)). No significant relationship was observed between HsCRP and allergic asthma or bronchial responsiveness. Conclusions: Raised levels of HsCRP are significantly associated with respiratory symptoms and non-allergic asthma but not with allergic asthma.